Patients' knowledge and attitudes about myocardial infarction. (14th August 2019) - Noureddine, Samar; Dumit, Nuhad Y.; Maatouk, Hassan
Abstract: Delay in seeking emergency care contributes significantly to the mortality associated with myocardial infarction. The aims of this descriptive study were to determine Lebanese patients' knowledge, attitudes, and beliefs about heart disease following their hospitalization for acute myocardial infarction, the factors associated, and to investigate the education they receive about heart disease. The study targeted 50 participants diagnosed with myocardial infarction who were interviewed about their knowledge, attitudes, and perceived control related to heart disease in their home 1 month after being discharged from hospital using the Acute Coronary Syndrome Response Index and the Control Attitude Scale–Revised. The findings showed inadequate knowledge, with only 26% scoring over 70%. Moreover, only 16% reported having received education about heart disease. The participants reported confidence in recognizing symptoms and getting assistance during a myocardial infarction. However, their beliefs regarding the importance of prompt seeking of emergency care for myocardial infarction and control over their disease were inconsistent. Patient education and counseling about recognizing and responding adequately to symptoms of myocardial infarction must be improved in both acute and primary healthcare settings.